Umbilical cord and cord blood cells promising for biobanking - V. V. Chrishtop; M. I. Lobanova; R. I. Glushakov; A. A. Semenov; D. V. Ovchinnikov; A. V. Anisin (Сибирский научный медицинский журнал)
Biobanks are created and operate in the interests of state security and the treatment of socially significant diseases. The high demand for biobanking of umbilical cord and cord blood has led to the emergence of specialized structures – Umbilical Cord Blood Banks. The aim was to systematize the literature data on the cellular composition of the umbilical cord and umbilical cord blood as an object of biobanking. Material and methods. The review includes literature sources containing data on the cellular composition of the umbilical cord and umbilical cord blood as an object of biobanking, provided by the eLibrary, PubMed, and Scopus databases. Results and discussion. Umbilical cord blood is significantly different from the blood of a newborn, even in the first hours of his life. The umbilical cord and umbilical cord blood contain stem cells (mesenchymal, hematopoietic, neural, very small embryonic-like, endothelial progenitors), differentiated cells of the hematogenous differon (monocytes, granulocytes, lymphocytes), as well as exosomes secreted by all of them. Differentiated cells of hematogenous differon are characterized by a decrease in phagocytic and cytotoxic activity, which is associated with the ability of mononuclear cell exosomes to inhibit inflammation, cell proliferation and cytokine production, and promote the transition from the Th1 or Th17 phenotype to the T-regulatory lymphocyte phenotype. Umbilical cord blood is a rich source of T cells with potent suppressive activity. Depending on the producing cell, exosomes may have different modulating characteristics. Mesenchymal stem cells of the umbilical cord are distinguished by high clonogenic potential, proliferative activity and a relatively low ability to differentiate towards the adipocyte lineage. The presence of neural stem cells in umbilical cord blood may explain the high effectiveness of cell therapy for damage to the nervous system using umbilical cord and umbilical cord blood. Conclusions. Biobanking of umbilical cord cells and umbilical cord blood is a promising area of regenerative medicine. The greatest prospects in the field of cell therapy and exosome production are opened by separate cryopreservation of mesenchymal, hematopoietic, neural and very small embryonic-like stem cells. A source of additional information for the development of this area can be the study of the natural microenvironment of stem cells - umbilical cord blood leukocytes, as well as the development of applied aspects of biobanking of umbilical cord and umbilical cord blood and annotation of the cellular composition of bio-samples.